Autonomous Off‐Equilibrium Morphing Pathways of a Supramolecular Shape‐Memory Polymer. Issue 34 (18th July 2021) - Peng, Wenjun; Zhang, Guogao; Zhao, Qian; Xie, Tao
Abstract: The diverse morphing behaviors of living creatures arise from their unlimited pathways. In contrast, the equilibrium‐driven morphing pathways of common synthetic shape‐shifting materials are very limited. For a shape‐memory polymer (SMP), its recovery from the temporary shape(s) to the permanent shape typically requires external stimulation and follows a single fixed route. Herein, a covalently crosslinked SMP is designed with ample ureidopyrimidinone (UPy) supramolecular moieties in the network. The UPy units endow the SMP with strong time–temperature dependency, which is explored as a mechanism for spatio‐temporal programming of autonomous shape‐shifting pathways. In particular, the use of digitally controlled photothermal heating provides versatility in control via an off‐equilibrium mechanism. In addition, cooling/heating across its glass transition introduces a locking/unlocking mechanism for its temporal morphing. The benefits of these unique features are demonstrated by multi‐shape‐transformation, an "invisible"‐color‐based clock, a time–temperature indicator, and sequence‐programmable 4D printing. Abstract : Highly designable autonomous morphing behaviors are achieved in a supramolecular shape‐memory polymer with strong time–temperature dependency. To prove the advantages of the molecular design, the benefits of the spatio‐temporal programming are demonstrated by off‐equilibrium multi‐shape‐transformation, self‐evolving sequence‐programmable 4D printing, an "invisible"‐color‐based clock, and a time–temperature indicator.